The cultural heritage of Colonia Nievas, Argentina: an analysis of its sociocultural sustainability - Giacomasso, María Vanesa (2026)
This paper aims to analyze the actions aimed at enhancing and ensuring thesustainability of the cultural heritage of Colonia Nievas (Buenos Aires, Argentina)during the 2021–2025 period. The research adopts an interdisciplinary approach that integrates anthropology and social communication. The methodology is qualitative, based on an ethnographic design. The main findings highlight the sociocultural sustainability of heritage through concrete context-specific policies of participatory and community-based management.